Corrosion Inhibition Behavior of DL-Methionine and L-Tryptophan on Carbon Steel - Achmad Rochliadi; Aep Patah; Claudia Claudia; Dadang Ramadhan (Jurnal Kimia Sains dan Aplikasi, 2023)
The cost-effective, efficient, and environmentally friendly corrosion inhibitors have become increasingly significant within the oil and gas sector. Consequently, this research was conducted to evaluate the corrosion inhibition behavior of the amino acids DL-Met and L-Tryp on carbon steel in acidic (0.05 M HCl), alkaline (0.05 M NH4OH), and neutral (3% NaCl) environments. This study used Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization (PDP) to assess the performance of amino acids as corrosion inhibitors. The EIS and PDP measurements revealed that DL-Met and L-Tryp exhibited corrosion inhibition effects exclusively in acidic conditions. In this environment, DL-Met demonstrated a corrosion inhibition efficiency (η) of 49.7% at a concentration of 525 ppm, while L-Tryp reached an efficiency of 87.08% at a concentration of 25 ppm. Under the same conditions, DL-Met reduced the corrosion rate from 10 mm/year to 4.468 mm/year, and L-Tryp reduced it from 10.95 mm/year to 5.003 mm/year. However, the corrosion inhibition activity of DL-Met and L-Tryp in neutral and alkaline conditions did not yield positive results according to EIS measurements. In neutral conditions, 100 ppm DL-Met exhibited -22.46% inhibitory activity. Meanwhile, in alkaline conditions, 150 ppm DL-Met and 5 ppm L-Tryp exhibited inhibition efficiencies of -72.39% and -81.9%, respectively. This research aims to provide the oil and gas industry with a natural-based corrosion inhibitor alternative, offering a solution to corrosion-related challenges in acidic conditions.